(3GdCTHGg hGdfXGFQ aj Gdabgs - (3Rjf GdOjf Hf EHQGgje Hf eMeO Hf fLje GdeUQj GdMfaj , GHf fLje,J (B970 (3g` s ((3Ydi Hf MSf Hf Ydi Hf MSf GdNhdGfi s)
(3ChdgG (B:s
(3GdMeO ddg Ydi eG CfYe hHYO aEf Gdabg CTQa GdYdhe bOQkG afTQY (B_ (3Ef TGA Gddg (B_ (3ai eG bUOfGg ef gPG GdJCdja HYO JSejJg H` JSejI dg HGSe HYV afhfg s
(3BNQgG (B:s
(3hbGd bWYc Gddg ceG bWYJ cJHi eG HJdi HGdCJQGc MJi LYdg Ydi QCS TLQJi aJbWY fUajf hgPG BNQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3eDWQI HGdMeQI s
(3cJHJ GdahGJM hGdYfGhjjf HGdMeQI s
(3HBNQgG JUMjM eDQN ai (B1038 (3g` s
Keywords: (3Gdabg GdESdGejs